GPT detectors are biased against non-native English writers - Liang, Weixin; Yuksekgonul, Mert; Mao, Yining; Wu, Eric; Zou, James (Patterns (New York, N.Y.), 2023)
GPT detectors frequently misclassify non-native English writing as AI generated, raising concerns about fairness and robustness. Addressing the biases in these detectors is crucial to prevent the marginalization of non-native English speakers in evaluative and educational settings and to create a more equitable digital landscape.